Hydrological response to long-lasting dry spell at the southern edge of Siberian permafrost - Han, Li; Menzel, Lucas (The science of the total environment, 2024)
Regions experiencing prolonged dry spell exhibit intensified land-atmosphere coupling, exacerbating dry conditions within the hydrological system. Yet, understanding the propagation of these processes within the context of permafrost degradation remains limited. Our study investigates concurrent hydro-climate variations in the semi-arid Selenga River basin in the southern edge of Siberian permafrost. Driven by the natural atmospheric circulations, this region experienced two distinct dry spells during 1954-2013. It enables comparative investigations into the role of warming-induced permafrost degradations in drought dynamics under land-atmosphere coupling. Based on a comprehensive analysis of observed borehole data from 1996 to 2009 and empirical methods, we identify widespread permafrost loss in the semi-arid Selenga region. Such large-scale landscape changes may increase the infiltration of water from the surface to the subsurface hydrological system, and significantly influence the dry conditions in landsurface. First, significant decreasing trends are observed in river runoff (−0.30mm/yr, p < 0.05) and TWS (−3.16 mm/yr, p = 0.1), despite the absence of an apparent trend in annual precipitation (0.009 mm/yr, p = 0.9). Furthermore, in comparison to the first dry spell (1974-1983, 10yrs), the hydro-climatic variables show prolonged and more severe water deficits in runoff and TWS during the second dry spell (1996-2012, 17 yrs), with a reduced runoff-generation efficiency from precipitation. Such exacerbated dry conditions are coincident with amplified positive anomalies observed in air temperature, PET, as well as low-level geopotential height. These concurrent “hot-dry” phenomena indicate an enhanced land-atmospheric interaction within the hydro-climate system, which is further evidenced by the negative relationship between permafrost thawing index and runoff deficits (regression coefficient = -3.8, p < 0.001). As climate warming continues, the ongoing permafrost degradation could reinforce water scarcity, triggering an irreversible shift in water availability in water-scarce regions. Our findings could support freshwater management for regional food supply, human health, and ecosystem functions in the regions undergoing large-scale permafrost degradation.
Gesehen am 05.06.2024